P511 Surveillance of Lymphogranuloma venereum among men who have sex with men attending STI clinics in alberta, canada, 2018. (14th July 2019) - Gratrix, Jennifer; Niruban, John; Severini, Alberto; Beirnes, Jennifer; Naidu, Prenilla; Chu, Angel; Singh, Ameeta; Smyczek, Petra
Abstract : Background: Lymphogranuloma venereum (LGV) is a sexually transmitted infection (STI) caused by Chlamydia trachomatis (CT) biovars L1-3, which has been increasingly reported among men who have sex with men (MSM). Our study aimed to establish a surveillance system among MSM attending STI clinics in Alberta, Canada to determine prevalence and characteristics of cases. Methods: CT NAAT (Genprobe Aptima COMBO 2® Assay) positive specimens from all anatomical sites among MSM attending three STI clinics between May to November 2018 had real-time PCR and DNA sequencing for LGV. Demographic, clinical, and sexual behaviours of cases were extracted from the provincial reporting database. Clinic-stratified analysis was performed to identify differences in sample characteristics using Chi-square or Fisher's exact test. Results: A total of 340 specimens from 299 CT cases were tested for LGV. CT cases were reported from Calgary (52.8%; n=158), Edmonton (46.2%; n=138), and Fort McMurray (1.0%; n=3). There were no significant differences in ethnicity, sexual partner type, anonymous partners, sex outside Alberta, or symptoms; however, cases from Calgary were significantly older than cases from Edmonton (median age: 34 years, IQR: 28–42 vs 29 years, IQR: 25–36, p=0.001) and more cases were co-infected with HIV (20.5% vs 10.0%; p=0.008). Anatomical site was similarly distributed between clinics with specimens from the rectum (61.2%; n=208), urine (26.2%; n=96) and pharynx (10.6%; n=36). LGV sequencing was feasible on 336 specimens. The LGV positivity rate was 1.2% (n=4; 95% CI 0.2–2.4); three rectal LGV cases (1 asymptomatic) and one asymptomatic pharyngeal LGV case were detected, of which two were HIV-positive. Conclusion: LGV was rare in our MSM population; however, one pharyngeal and one asymptomatic case were found. If untreated, these cases could serve as a reservoir and play an important role in transmission. Disclosure: No significant relationships.